PENERAPAN INFORMATION RETRIEVAL PADA SEARCH ENGINE - NURAINI AHMAD; ARIENDA ADDIS PRASETYO; ANIS MASRURI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
Information retrieval (information retrieval), while it has been applied in various fields of human life. Library, museum, document management, knowledge management, collection management, records management has been known before the web search engines (search engine website, often referred to as search engines only) applied. The Web as a medium that would later appear, it requires also a model retrieval system of its own. Before the use of a search engine website that is known at this time, experts of the library has been trying to apply the principles of categorization and classification as they arrange the collection of the library. However, it turns out that the website has its own characteristics, so the model that they develop quickly outdated. The Website has the properties of fast-changing and temporary. In this paper, the authors discuss how the implementation of information retrieval in search engines. The results showed that search engines continue to evolve to provide information that is relevant to the development of the evaluation process, improving the ability, update data, continue to adapt to users ' needs, improve the ability of the performance of the device, and try to solve the problem encountered. ABSTRAKInformation retrieval (temu kembali informasi), saat ini telah diterapkan dalam berbagai bidang kehidupan manusia. Perpustakaan, museum, manajemen dokumen, manajemen pengetahuan, manajemen koleksi, manajemen arsip telah dikenal sebelum web search engine (mesin pencari website, sering disebut dengan search engine saja) diterapkan. Web sebagai media yang belakangan muncul, membutuhkan pula model sistem temu kembali tersendiri. Sebelum digunakannya mesin pencari website yang dikenal saat ini, para ahli perpustakaan telah mencoba menerapkan prinsip-prinsip kategorisasi dan klasifikasi sebagaimana mereka mengatur koleksi perpustakaan. Namun, ternyata website mempunyai karakteristik sendiri, sehingga model yang mereka kembangkan dengan cepat ketinggalan zaman. Website mempunyai sifat cepat berubah dan sementara. Dalam tulisan ini, penulis mendiskusikan bagaimana penerapan information retrieval pada search engine. Hasil penelitian menunjukkan bahwa search engine terus berkembang untuk menyediakan informasi yang relevan dengan pengembangan proses evaluasi, meningkatkan kemampuan, memperbarui data, terus beradaptasi dengan kebutuhan pengguna, meningkatkan kemampuan kinerja perangkat, dan berusaha menyelesaikan masalah yang dihadapi.